Target Setting in Teacher Career Development: Analysis of Human Resource Management SMART Model - Rismita, Rismita; Muljono, Hery (Journal of Educational Science and Technology (EST), 2023)
This study aims to analyze the effect of target setting management on the academic development of teacher careers. This study uses a quantitative method with a survey approach. The sample technique is a systematic sampling based on the order of teacher data as many as 108 respondents. Data collection is done by distributing questionnaires through googleform. Data analysis was carried out with validity and reliability tests, linear regression analysis. The results of the study obtained the value of the correlation coefficient which was included in the sufficient category, and a positive value, and there was a significant influence between the target setting variables on the academic development of teacher careers. Determination of target settings in the form of increasing knowledge and skills refers to the SMART model that can be used by teachers to achieve success in career development.